РЕЗУЛЬТАТЫ ПСИХОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ ПРОБЛЕМ МЕЖЛИЧНОСТНЫЕ ОТНОШЕНИЯ МЛАДШИХ ШКОЛЬНИКОВ - Клычева, З.П. (SCIENCE and SOCIETY, 2024)
This article presents the results of psychological research on communication problems, as well as interpersonal relationships that occur in communication between elementary school pupils. The research was conducted in schools of Nukus, Republic of Karakalpakstan, with 2nd-4th grade pupils.